Revolutionizing Malaysian terrace housing design by adopting Islamic visual privacy principles: a pilot study on Malay occupants - Abd Manaf, Azhani; Abdul Rahim, Zaiton; Abdul Majid, Noor Hanita; Spahic, Omer (Metin Copy Plus, Mollafenari Mah., 2017)
This paper focuses on the problem of lack of visual privacy in current Malaysian terrace housing designs, especially for Malay occupants. The Malay family is central to the study due to particular regulations and principles regarding modesty of self and protection of awrat imposed by Islam. Although past literature highlighted this issue of lack of visual privacy in terrace housing, there is an insufficient explanation on its specific definition and application to the Malay Muslim family. This pilot study is part of larger research towards developing a framework and guideline on the application of visual privacy from Islamic perspective henceforth termed as Muslim Visual Privacy (MVP). One of its main objectives is to investigate how MVP is applied, adapted and perceived by the typical Malay family of terrace housing in Malaysia due to its various constraints. Thus, this paper sought to begin unravelling the perception and application of MVP among Malay families residing in terrace housing by discussing on the pilot study stage of the research. It touches on the data collection process, analysis and discussion of the pilot study. Utilizing a mixed method approach for a more holistic and meaningful result, the actual data collection chose to use a combination of questionnaire survey consisting of 32 main questions and case study method (in-depth interview, graphic documentation and observation). However, for this paper, the author focuses on the pilot study stage in which the main instrument utilised and analysed is a questionnaire survey form. The survey interview was carried out on 44 households sampled from the Malay population residing in terrace housing. The findings show that based on literature review, there are three categories of visual privacy elements from an Islamic perspective which are site, plan and outdoor, each with their own specific elements. Data also indicates that in order to provide visual restriction, Malay families need to sacrifice visual access and social elements which are equally important sociocultural factors. The study contributes to further improvement of the set of MVP characteristics in making terrace housing more suitable for Malay families.